GROUND-WATER RESOURCES ASSESSMENT USING GEOPHYSICAL VLF METHOD: A CASE STUDY FROM WATER RESOURCES ASSESSMENT USING GEOPHYSICAL VLF METHOD: A CASE STUDY FROM WATER RESOURCES ASSESSMENT USING GEOPHYSICAL VLF METHOD: A CASE STUDY FROM COASTAL URBAN FOREST - Nazli Ismail (Jurnal Natural, 2013)
In urban areas, there is not only a heavy reliance on ground water as a primary drinking supply but is also as a supply of water for both agriculture and industrial uses. The reliance on ground water is necessary to ensure that there are significant quantities and high quality of water. Ground water resources at coastal urban forest in Banda Aceh were assessed by using VLF method. VLF techniques measured the perturbations in a plane wave radio signal (15-30 kHz) being emanated from one of several world-widde radio transmitters and was also used for submarine communications. Apparent resistivities and phases were measured along 340 m profile at the area. Two frequencies (27700 and 29000 Hz) were used in this measurement. The data were modeled by using 2D inversion code of Rebocc. The model showed clearly ground-water map of the subsurface. Based on the model, aquifer layers were indicated by low resistivities zones (40 – 400 Ω-m). However, the ground-water resources in the area were dominated with high salinity water at depth under 140 m. Therefore, extended geophysical exploration methods were water aquifer in the area to watering the forest.